Some Results on Projective Curvature Tensor of Nearly Cosymplectic Manifold (European Journal of Pure and Applied Mathematics, 2018)
In the nearly cosymplectic manifold, dened a tensor of type (4,0), it's called a projective curvature tensor. In this article we discuss an interesting question; what the geometric meaning of this tensor when it's act on nearly cosymplectic manifold? The answer of this question leads to get an application on Einstein space. In particular, the necessary and sucient conditions that a projective tensor is vanishes are found.
Keywords: Projective curvature tensor; Almost contact manifold; Nearly cosplectic manifoldym